National referral mechanism and duty to notify statistics, 2014-2024 (UK Data Service, 2024)
Modern slavery is a term that includes any form of human trafficking, slavery, servitude or forced labour, as set out in the Modern Slavery Act 2015. Potential victims of modern slavery in the UK that come to the attention of authorised ‘First Responder’ organisations are referred to the National Referral Mechanism (NRM). Adults (aged 18 or above) must consent to being referred to the NRM, whilst children under the age of 18 need not consent to being referred. As specified in section 52 of the Modern Slavery Act 2015, public authorities in England and Wales have a statutory duty to notify the Home Office when they come across potential victims of modern slavery ('Duty to Notify' (DtN)). This duty is discharged by either referring a child or consenting adult potential victim into the NRM, or by notifying the Home Office via the DtN process if an adult victim does not consent to enter the NRM. The Home Office publishes quarterly statistical bulletins and aggregated data breakdowns on the National Referral Mechanism webpage on the GOV.UK website regarding the number of potential victims referred each quarter. To allow stakeholders and first responders more flexibility in analysing this data for their own strategic and operational planning, the disaggregated, pseudonymised dataset used to create the aggregated published data is also available from the UK Data Service as 'safeguarded' data. (The UKDS data are available in SPSS, Stata, tab-delimited text and CSV formats.) For the 14th edition (November 2024), the data file was amended to include Quarter 3 2024 cases (up to 4 October), and the Data Notes documentation file was also updated.